Fabrication of flexible indium tin oxide-free polymer solar cells with silver nanowire transparent electrode. (19th February 2018) - Lin, Ming-Yi; Chen, Tsun-Jui; Xu, Wei-Feng; Hsiao, Li-Jen; Budiawan, Widhya; Tu, Wei-Chen; Chen, Shih-Lun; Chu, Chih-Wei; Wei, Pei-Kuen
Abstract: Flexible indium tin oxide (ITO)-free poly(3-hexylthiophene):[6, 6]-phenyl C61-butyric acid methyl ester (P3HT:PC61 BM) solar cells with a spin-coated silver nanowire transparent electrode are demonstrated. The solution-processed silver nanowire thin film not only exhibits high transmission (∼87%), but also shows low sheet resistance R s (∼25 Ω/sq). For solar cells with a conventional structure, the power conversion efficiency (PCE) of devices based on silver nanowires can reach around 2.29%. For the inverted structure, the PCE of devices can reach 3.39%. Conventional and inverted flexible ITO-based P3HT:PC61 BM solar cells are also fabricated as a reference for comparison. For both types of solar cells, the PCE of ITO-free devices is very close that of an ITO-based polymer solar cell.